The Effects of Transcranial Electrical Stimulation of the Brain on Sleep: A Systematic Review - Dondé, Clément; Brunelin, Jerome; Micoulaud-Franchi, Jean-Arthur; Maruani, Julia; Lejoyeux, Michel; Polosan, Mircea; Geoffroy, Pierre A. (Frontiers in Psychiatry, 2021)
Transcranial Electrical Stimulation (tES) is a promising non-invasive brain modulation tool. Over the past years, there have been several attempts to modulate sleep with tES-based approaches in both the healthy and pathological brains. However, data about the impact on measurable aspects of sleep remain scattered between studies, which prevent from drawing firm conclusions. We conducted a systematic review of studies that explored the impact of tES on neurophysiological sleep oscillations, sleep patterns measured objectively with polysomnography and subjective psychometric assessments of sleep in both healthy and clinical samples. We searched four main electronic databases to identify studies until February 2020. Forty studies were selected including 511-healthy participants and 452-patients. tES can modify endogenous brain oscillations during sleep through possible modulation of cortico-thalamo-cortical networks. Results concerning changes in sleep patterns are conflicting, whereas subjective assessments show clear improvements after tES. Although these findings cannot be directly transferred to the clinical practice and sleep-enhancing devices development for healthy populations, they might help to pave the way for future researches in these areas.